Development Of Novel Microsatellite Markers And Assessment Of Population Genetics In The Tropical Bed Bug, Cimex Hemipterus F. (Hemiptera: Cimicidae) - Mohammad, Wan Nur Fatanah Wan (2020)
Bed bug infestations are on the rise in Malaysia. The tropical bed bug, Cimex hemipterus (Fabricius) is a nocturnal blood-sucker that is predominant in the tropical region. Despite its alarming infestation rate, the information on its population genetics remains scarce. To infer this, the study is aimed at developing and characterizing novel microsatellite markers from the genome of C. hemipterus and to assess population genetics within Malaysia and Singapore based on the newly developed microsatellite markers and mitochondrial DNA (mtDNA) genes namely cytochrome oxidase I (COI) and 16S ribosomal deoxyribonucleic acid (16S rDNA). Here, the next generation 454 Roche pyrosequencing technique was used to develop the novel microsatellite markers. A total of 52,119 reads with 1,821 (3.49%) reads containing microsatellites with di-, tri- and tetra-nucleotide repeat motifs were obtained. Eight primers were used to assess the population genetics of C. hemipterus within Malaysia and Singapore. 351 individuals of C. hemipterus were genotyped across eight polymorphic microsatellite loci. All populations in this study showed heterozygosity deficit, except BMV (observed heterozygosity, HO = 0.71; expected heterozygosity, HE = 0.62). Nonetheless, a low to moderate level of genetic diversity was observed across all populations (allelic richness, AR : 1.85 - 3.75; the number of alleles per locus, NA = 1.88 – 3.88). The allele frequency distribution displayed that the populations of the tropical bed bug in this study were experiencing recent bottleneck and it was supported by the value of Garza-Williamson (GW) index.